OCEAN GREEN SCIENCE DISTRICT IN SURABAYA: A MARINE SCIENCE HUB WITH A FUTURISTIC APPROACH - Wahyu Kurniawan; Nurhamdoko Bonifacius; Raqyan Mas Bimatyugra Jati (Architecture Study Program, Faculty Of Engineering, University of Merdeka Malang, 2025)
This architectural design project proposes the Ocean Green Science District in Surabaya, a marine research center that integrates sustainability, smart technology, and futuristic architectural expression. The selection of Surabaya’s coastal area as the site reflects its strategic location in supporting national marine research, education, and innovation. The design is guided by a contextual, functional, and morphological approach, aiming to harmonize the building with the coastal environment while also responding to urban dynamics. The main concept, “A Futuristic Harmony of Marine Science,” is translated through a combination of fluid building forms, wave-inspired facades, and smart green infrastructure. The project is divided into two building masses: Aegir, the high-rise research tower that symbolizes strength and knowledge of the sea, and Ranalia, the supporting low-rise complex that embraces openness and adaptability. Together, they form a unified marine science hub connected by an eco-corridor and sky bridge system. This project emphasizes not only environmental and technological integration, but also architectural storytelling that represents the depth and dynamism of the ocean. The result is a research facility that is visionary, functional, and responsive to the future of marine science.